Determinasi Faktor Fundamental Makroekonomi dan Indeks Harga Saham Syariah Internasional terhadap Indeks Harga Saham Syariah Indonesia - Yudhistira Ardana; Siska Maya (Cakrawala: Jurnal Studi Islam, 2019)
The capital market is a source of fresh funds in the long and short-term. The existing of the institution is not only a source of funding but also as an investment facility. This study aims to measure the impact of macroeconomic conditions (BI Rate, Exchange Rate and World Oil Prices) and the international Sharia stock index (Dow Jones Islamic Market Index Japan and Dow Jones Islamic Market Index US) on the Indonesian Sharia Stock Index with using the error correction model (ECM). The results showed that BI rate and DJIM US have the significant effect (5%) on Indonesian Sharia Stock Index in the short, while the exchange rate and DJIM Japan are significant at the 10%, and the world oil price is not significant. In the long-term, BI Rate, exchange rate, DJIM US and DJIM Japan have a significant effect, while the world oil price has not a significant effect.